Losing seasonal patterns in a hibernating omnivore? Diet quality proxies and faecal cortisol metabolites in brown bears in areas with and without artificial feeding - Sergiel, Agnieszka (PLoS One, 2020)
Bears are omnivores particularly well-adapted to variations in the nutritional composition, quality and availability of food resources. Artificial feeding practices have been shown to strongly influence diet composition and seasonality, as well as to cause alterations in wintering and movement in brown bears (Ursus arctos). In this study, we investigated seasonal differences (hypophagia vs hyperphagia) in food quality of two brown bear subpopulations in the Polish Carpathians using faecal nitrogen (FN) and carbon (FC) estimates. The subpopulations inhabit areas that differ in artificial feeding practices: no artificial feeding occurs in the western subpopulation (Tatra Mountains), while artificial food targeted to ungulates is provided and used year-round in the eastern subpopulation (Bieszczady Mountains). We also compared these results with faecal cortisol metabolites (FCM) to explore how FN and FC correlate with the hypothalamic-pituitary-adrenal axis activity and if the seasonal patterns are apparent. We found that in Tatra Mts bears fed on significantly higher quality diet, as shown by FN and FC values, and had significantly higher FC levels in hyperphagia, when they accumulate fat reserves for wintering. The pattern in FCM levels for Tatra subpopulation followed the changes in energy intake during the seasons of hypo- and hyperphagia, while in Bieszczady Mts, the area with intensive feeding, no seasonal patterns could be observed. Artificial feeding practices may disrupt nutrient phenology and seasonality, relative to subpopulations with natural diets. We showed that the availability of human-provided foods may alter not only the overall dietary quality, but also hormonal patterns linked to seasonal nutritional requirements. Combining FN, FC and FCM proved to be a useful tool for reconstructing diet quality and related physiological patterns.